2021
DOI: 10.1093/mnras/stab883
|View full text |Cite
|
Sign up to set email alerts
|

3D simulations of oxygen shell burning with and without magnetic fields

Abstract: We present a first 3D magnetohydrodynamic (MHD) simulation of convective oxygen and neon shell burning in a non-rotating 18 M⊙ star shortly before core collapse to study the generation of magnetic fields in supernova progenitors. We also run a purely hydrodynamic control simulation to gauge the impact of the magnetic fields on the convective flow and on convective boundary mixing. After about 17 convective turnover times, the magnetic field is approaching saturation levels in the oxygen shell with an average f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 121 publications
0
14
0
Order By: Relevance
“…If this kind of angular momentum transport occurs in earlier stages, outward transport of the angular momentum will be suppressed and the stars might keep larger angular momentum. Recently, a 3D magnetohydrodynamic simulation of oxygen-shell burning has been investigated (Varma & Müller 2021). Although they found that magnetic fields do not appreciably alter the convective flow, the fields might affect the angular momentum transport in convection layers.…”
Section: Profile Of Specific Angular Momentummentioning
confidence: 99%
“…If this kind of angular momentum transport occurs in earlier stages, outward transport of the angular momentum will be suppressed and the stars might keep larger angular momentum. Recently, a 3D magnetohydrodynamic simulation of oxygen-shell burning has been investigated (Varma & Müller 2021). Although they found that magnetic fields do not appreciably alter the convective flow, the fields might affect the angular momentum transport in convection layers.…”
Section: Profile Of Specific Angular Momentummentioning
confidence: 99%
“…In particular, it would be desirable to investigate the implications for detailed nucleosynthesis yields rather than just considering the 𝑌 e -distributions in our current study. While MHD supernova simulations still need to further mature in many respects, e.g., by considering more realistic initial magnetic field configurations (Varma & Müller 2021), further code comparisons will be an important tool on the long road towards a robust understanding of the role of magnetic fields in the explosions of massive stars.…”
Section: Discussionmentioning
confidence: 99%
“…Initial conditions for magnetorotational explosion simulations currently come from "1.5D" stellar evolution models that assume shellular rotation and include effective recipes for magnetic field generation and angular momentum transport by hydrodynamic and magnetohydrodynamic processes (Heger et al 2000(Heger et al , 2005Woosley & Heger 2006). Efforts to better understand the angular momentum distribution and magnetic fields in the cores of massive stars by means of multi-dimensional simulation have only started recently (Varma & Müller 2021;Yoshida et al 2021;McNeill & Müller 2021). Since 1.5D stellar evolution models predict magnetic fields that are rather weak and predominantly toroidal, the general notion has long been that field amplification processes after collapse are critical in magnetorotational explosions, although this has recently been challenged (Obergaulinger & Aloy 2017.…”
Section: Introductionmentioning
confidence: 99%
“…In this scenario, the timing of the mass-loss should correspond to late stages of nuclear burning, which occurs on timescales of days to weeks prior to explosion for silicon burning; to several months for neon burning; to several years for oxygen burning (e.g., Woosley et al 2002). Another mechanism for gen-erating pre-SN mass-loss invokes sudden energy release deep inside the star due to instabilities associated with late-stages of nuclear shell burning (e.g., Meakin & Arnett 2007;Smith & Arnett 2014;Fields & Couch 2021;Varma & Müller 2021;Yoshida et al 2021). Mass-loss due to interaction with a close binary companion may also play a role in some events (e.g., Chevalier 2012;Sun et al 2020).…”
Section: Introductionmentioning
confidence: 99%